The Influence of Transformational Leadership on Organizational Culture : The Case of Food and Beverage Employees in Indonesia - Muhammad Ali Al Ihsan; Rizki Syahputra; Alwi Muhammad Adam (Garuda Prestasi Nusantara Consulting, 2021)
The purpose of this study was to determine the effect of transformational leadership on organizational culture. The research was conducted on Small and Medium Enterprises in the Food and Minimum Industry Sector in Medan City. The sample in this study were employees in the Food and Minimum Industry Sector in Medan City. 350 questionnaires were distributed, 188 were returned. Thus the participants in this study amounted to 188 people. The data is carried out with Structural Equation Modeling. The results show that transformational leadership can improve the corporate culture of the food and beverage industry in Medan City. Suggestions in this study are for the owner as the owner to improve leadership and good organizational culture.